TAXES AND SOCIAL COSTS (Tufts Archival Research Center, 2007)
Report on legislative activity surrounding taxes and social costs of smoking for May 1993. Argues that it is unlikely that excise tax will be introduced for budget reconciliation, but may be introduced as financing mechanism for health care reform. Discusses work with allies on state and federal lobbying, monitoring of health care reform, activity with allies to encourage progressively-financed health care reform, and attempts to refute social cost argument.